Master track of MARIA S. MERIAN cruise MSM137 in 1 sec resolution (zipped, 123 MB) - Schnabel, Michael (Federal Institute for Geosciences and Natural Resources, 2025)
Raw data acquired by position sensors on board RV MERIAN during expedition MSM137 were processed to receive a validated master track which can be used as reference of further expedition data. During MSM137 the motion reference unit Kongsberg SeaTex AS MRU-5 combined with Kongsberg SeaTex AS Seapath 320 and the GPS receivers Trimble SPS855 and SAAB R4 were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.
Keywords: 1 sec resolution